Preparation method of bimetallic iron-based chitosan adsorbent and application of bimetallic iron-based chitosan adsorbent in removal of As (III) in water

By combining chitosan with iron and other metal elements, bimetallic iron-based chitosan adsorbent was prepared, which solved the problem of poor performance of iron-based adsorbent in adsorbing As(III) and achieved efficient adsorption of As(III) in water.

CN119746824APending Publication Date: 2025-04-04SHIHEZI UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411745951.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Iron-based chitosan adsorbents do not perform well in adsorbing As(III) and are difficult to meet the need to remove arsenic pollution in water.

Method used

The preparation method of bimetallic iron-based chitosan adsorbent is adopted to form a composite metal oxide adsorbent by combining chitosan with iron and other metal elements (such as lanthanum, zirconium, manganese), thereby improving its adsorption ability to As(III).

Benefits of technology

It realizes efficient adsorption of As(III) in water, improves the adsorption capacity and recycling ability of the adsorbent, avoids the leaching of metal ions, and prevents secondary contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746824A_ABST
    Figure CN119746824A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bimetallic iron-based chitosan adsorbent and application of the bimetallic iron-based chitosan adsorbent in removal of As (III) in water. Comprising the following steps: (1) dissolving chitosan powder in an acetic acid solution, and continuously stirring until the chitosan powder is completely dissolved to obtain a faint yellow chitosan solution; (2) pouring a metal mixed solution (an iron-lanthanum metal mixed solution, an iron-zirconium metal mixed solution and an iron-manganese metal mixed solution) into the chitosan solution, and continuously stirring for 0.5-1 hour to obtain a metal ion / chitosan mixed solution; (3) slowly dropwise adding a precipitator into the metal ion / chitosan mixed solution to precipitate chitosan until the pH value of the mixed solution is 7.0 + / -0.1 to obtain a chitosan suspension; (4) continuously stirring the suspension obtained in the step (3) for 1.5 hours by using a stirrer; (5) putting the suspension after stirring into a water bath kettle to be subjected to constant-temperature water bath at 60 DEG C for 24 hours; and (6) centrifuging the suspension after the water bath, pouring out the supernatant to obtain a chitosan precipitate, cleaning the precipitate for three times, freeze-drying for 24 hours, grinding into powder, and sieving with a 200-mesh sieve to obtain the bimetallic iron-based chitosan adsorbent. Compared with an iron-based chitosan adsorbent, the bimetallic iron-based chitosan adsorbent prepared by the preparation method disclosed by the invention has stronger adsorption performance on As (III), and the adsorption capacity of the bimetallic iron-based chitosan adsorbent is as high as 50.80 mg / g. The water body application range is wide, the adsorbent is suitable for different pH environments (3.0-11.0), the preparation method of the adsorbent is simple, materials are easy to obtain, and the adsorbent is especially suitable for remote distributed water supply areas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of As(III) treatment in water, and in particular to a preparation method of a bimetallic iron-based chitosan adsorbent and an application thereof in removing As(III) from water. Background Art

[0002] Arsenic is a highly toxic carcinogen that is widely present in the environment. Arsenic pollution in water bodies is a global problem and poses a serious threat to public health in many countries. Long-term exposure to arsenic-containing water can cause health problems such as systemic organ failure, epilepsy, coma, neurological disorders, and cancer. To ensure the safety of drinking water, the World Health Organization (WHO) and my country's "Sanitary Standards for Drinking Water" (GB 5749-2022) stipulate that the limit of arsenic content in drinking water is 10μg / L.

[0003] In recent decades, people have been committed to developing arsenic removal technologies, including coagulation, adsorption, ion exchange, membrane separation, etc. It is worth noting that the adsorption method is suitable for small and medium-sized towns and rural areas with incomplete water treatment facilities due to its simple operation and high cost-effectiveness. The adsorption performance of the adsorbent is the core of the adsorption technology, and various natural or synthetic adsorbents have been used to remove arsenic. Iron-based chitosan is an adsorption material that combines iron oxide with chitosan. It is not only easy to obtain raw materials and low cost, but also has a strong affinity for arsenic.

[0004] Research in recent years has revealed the limitations of single-metal adsorbents in treating As(III). In particular, iron-based adsorbents perform poorly in adsorbing As(III). To overcome this challenge, researchers have proposed an innovative strategy to improve the adsorption efficiency of adsorbents by combining them with other metal elements to form composite metal oxide adsorbents. For example, the introduction of lanthanum and zirconium can significantly increase the adsorption capacity of the adsorbent, and the introduction of manganese and titanium can give the adsorbent oxidation ability, converting As(III) into more easily adsorbed As(V), thereby improving the overall adsorption efficiency. This multi-metal composite strategy not only broadens the application range of adsorbents, but also provides a new perspective for the development of water treatment technology. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of iron-based chitosan, the present invention provides a method for preparing a bimetallic iron-based chitosan adsorbent. The method of the present invention has easy-to-obtain raw materials, a simple preparation method, a high adsorption capacity, and can efficiently adsorb As(III) in water.

[0006] The preparation method of a bimetallic iron-based chitosan adsorbent and its application in removing As(III) from water include the following steps:

[0007] (1) dissolving chitosan powder in acetic acid solution and stirring continuously until completely dissolved to obtain a light yellow chitosan solution;

[0008] (2) pouring the same volume of metal mixed solution (iron-lanthanum, iron-zirconium, iron-manganese metal ion mixed solution) as the chitosan solution into the chitosan solution, and stirring continuously for 0.5 to 1 h to obtain a metal ion / chitosan mixed solution;

[0009] (3) slowly adding a precipitant to the metal ion / chitosan mixture to precipitate chitosan until the pH of the mixture reaches 7.0±0.1, thereby obtaining a chitosan suspension;

[0010] (4) stirring the suspension obtained in step (3) continuously for 1.5 h with a stirrer;

[0011] (5) After stirring, the suspension was placed in a water bath at 60°C for 24 h;

[0012] (6) The suspension after water bath was centrifuged, and the supernatant was discarded to obtain chitosan precipitate. The precipitate was washed three times and then freeze-dried for 24 hours, ground into powder and passed through a 200-mesh sieve to obtain a bimetallic iron-based chitosan adsorbent.

[0013] The concentration of the chitosan solution in step (1) is 10-60 g / L, and the concentration of the acetic acid solution is 1%-5%. The metal mixed solution in step (2) includes three types, namely, iron-lanthanum, iron-zirconium, and iron-manganese metal ion mixed solutions, and the preparation method is: weigh a certain amount of iron salt and lanthanum salt, zirconium salt or potassium permanganate and dissolve them in the acetic acid solution in step (1). The iron salt is ferric chloride or ferric nitrate, the lanthanum salt is lanthanum chloride or lanthanum nitrate, and the zirconium salt is zirconium oxychloride; the concentration of the iron salt is 0.12 mol / L; the molar ratio of the iron salt to the lanthanum salt, zirconium salt or potassium permanganate is 1:1-8:1.

[0014] The precipitant in step (3) is NaOH or KOH solution with a concentration of 0.5 to 5 mol / L.

[0015] The three times of washing in step (6) refers to washing three times with anhydrous ethanol and deionized water respectively.

[0016] The continuous stirring speed in steps (1)-(4) is 100 to 300 rpm.

[0017] The bimetallic iron-based chitosan adsorbent is obtained by the above preparation method.

[0018] The above-mentioned bimetallic iron-based chitosan adsorbent is used to remove As(III) in water.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention adopts a "sol-gel-drying" preparation process to prepare a bimetallic iron-based chitosan adsorbent, the preparation method is simple, the raw materials are easily available, and the adsorbent has high application potential; the present invention introduces other types of metals into the iron-based chitosan adsorbent, combines the advantages of chitosan and different metals, and improves the adsorption capacity of the adsorbent for As(III); due to the cross-linking effect of chitosan on metal ions, the chemical properties are stable, which not only enhances its recycling capacity, but also can effectively avoid the leaching of metal ions when applied to groundwater arsenic removal, preventing the metal leaching from causing secondary pollution to the treated water. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the preparation process of bimetallic iron-based chitosan adsorbent.

[0022] Figure 2 This is a graph showing the adsorption effect of a lanthanum-loaded bimetallic iron-based chitosan adsorbent (A3) on different concentrations of As(III) in water.

[0023] Figure 3 This is a diagram showing the adsorption effect of lanthanum-loaded bimetallic iron-based chitosan adsorbents (A0, A1, A2, A3, A4) with different metal molar ratios on As(III) in water.

[0024] Figure 4 This is a diagram showing the adsorption effect of bimetallic iron-based chitosan adsorbents (A0, A2, A5, A6) loaded with different types of metal ions on As(Ⅲ) in water.

[0025] Figure 5 The adsorption capacity of a lanthanum-loaded bimetallic iron-based chitosan adsorbent (A3) and an iron-based chitosan adsorbent (A0) for As(III) at different pH values. DETAILED DESCRIPTION

[0026] The present invention is further described below in conjunction with preferred embodiments and the accompanying drawings, but the protection scope of the present invention is not limited thereto.

[0027] In the embodiments of the present invention, unless otherwise specified, the methods used are all conventional methods, and the materials used can be purchased from commercial sources.

[0028] Example 1

[0029] The adsorption capacity of a lanthanum-loaded bimetallic iron-based chitosan adsorbent (A3) of the present invention for different concentrations of As(III) in water is investigated, comprising the following steps:

[0030] Weigh 0.03 g of a lanthanum-loaded bimetallic chitosan adsorbent (A3) and add it to 30 ml of 20, 40, 60, or 80 mg / LAs(III) solution (pH = 7.0 ± 0.1). Adsorb it in a constant temperature water bath oscillator for 24 h (25 ° C, 150 rpm). After filtering the water sample through a 0.45 μm filter membrane, the arsenic concentration is determined.

[0031] In this embodiment, a method for preparing a lanthanum-loaded bimetallic iron-based chitosan adsorbent (A3) is as follows:

[0032] (1) Dissolve 1 g of chitosan powder in 50 ml of 2% acetic acid solution and stir continuously until it is completely dissolved to obtain a light yellow chitosan solution;

[0033] (2) dissolving 0.006 mol of ferric chloride and 0.0045 mol of lanthanum chloride (the molar ratio of iron to lanthanum is 4 / 3) in 50 ml of 2% acetic acid solution, pouring the iron-lanthanum metal solution into the chitosan solution and stirring continuously for 0.5 to 1 g to obtain an iron-lanthanum / chitosan mixed solution;

[0034] (3) slowly adding 3 mol / L sodium hydroxide solution to the iron-lanthanum / chitosan mixture until the pH reaches 7.0±0.1 to obtain an iron-lanthanum / chitosan suspension;

[0035] (4) stirring the iron-lanthanum / chitosan suspension continuously for 1.5 h using a stirrer;

[0036] (5) After stirring, the suspension was placed in a water bath at 60°C for 24 h;

[0037] (6) After the water bath, the suspension was centrifuged, and the supernatant was discarded to obtain chitosan precipitate. The precipitate was washed three times and then freeze-dried for 24 hours, ground into powder and passed through a 200-mesh sieve to obtain a lanthanum-loaded bimetallic iron-based chitosan adsorbent (A3).

[0038] In this example, the adsorption effect of adsorbent A3 on As(III) at different concentrations in water was compared. Figure 1 As shown. Figure 1 It can be seen that with the increase of the initial concentration of As(Ⅲ), the adsorption amount of As(Ⅲ) by adsorbent A3 becomes larger and larger, and the removal rate gradually decreases. When the initial As(Ⅲ) concentration is lower than 40 mg / L, a high removal rate (removal rate>90%) can be maintained.

[0039] Example 2

[0040] The adsorption capacity of the lanthanum-loaded bimetallic chitosan adsorbent of the present invention for As(III) was investigated with different metal molar ratios, comprising the following steps:

[0041] Weigh 0.03 g of lanthanum-loaded bimetallic chitosan adsorbent (A0, A1, A2, A3, A4) and add it to 30 ml of 40 mg / LAs(Ⅲ) solution (pH = 7.0 ± 0.1), adsorb in a constant temperature water bath oscillator for 24 h (25 ° C, 150 rpm), and determine the arsenic concentration after filtering the water sample through a 0.45 μm filter membrane.

[0042] In this embodiment, the preparation method of the lanthanum-loaded bimetallic iron-based chitosan adsorbents A0, A1, A2, and A4 used is basically the same as that of A3, with the only difference being that when preparing adsorbent A0, no lanthanum salt is added in step (2), when preparing adsorbent A1, the amount of lanthanum salt added in step (2) is 0.0015 mol (the molar ratio of iron to lanthanum is 4 / 1), when preparing adsorbent A2, the amount of lanthanum salt added is 0.003 mol (the molar ratio of iron to lanthanum is 2 / 1), and when preparing adsorbent A4, the amount of lanthanum salt added is 0.006 mol (the molar ratio of iron to lanthanum is 1 / 1).

[0043] In this example, the adsorption effect of lanthanum-loaded bimetallic iron-based chitosan adsorbents with different metal molar ratios on As(III) in water was compared. Figure 2 As shown. Figure 2 It can be seen that with the increase of the iron-lanthanum molar ratio, the adsorption amount and removal of As(III) by the material first increase and then decrease. The adsorption efficiency of As(III) is optimal when the iron-lanthanum molar ratio is 4 / 3.

[0044] Example 3

[0045] In this embodiment, the adsorbents used include an iron-based chitosan adsorbent (A0), a lanthanum-loaded bimetallic iron-based chitosan adsorbent (A2), a lanthanum-loaded bimetallic iron-based chitosan adsorbent (A5), and a manganese-loaded bimetallic iron-based chitosan adsorbent (A6).

[0046] The adsorption capacity of different types of metal ion-loaded bimetallic iron-based chitosan adsorbents (A0, A2, A5, A6) of the present invention on As(III) in water was investigated, comprising the following steps:

[0047] Weigh 0.03g of different types of metal ion-loaded bimetallic chitosan adsorbents (A0, A2, A5, A6) and add them into 30ml of 40mg / LAs(Ⅲ) solution (pH=7.0±0.1). Adsorb them in a constant temperature water bath oscillator for 24h (25℃, 150rpm). After filtering the water sample through a 0.45μm filter membrane, the arsenic concentration is determined.

[0048] In this embodiment, the preparation method of adsorbents A5 and A6 used is basically the same as that of adsorbent A2 in Example 1, with the only difference being that when preparing adsorbent A5, the metal salt added in step (2) is 0.006 mol ferric chloride and 0.003 mol zirconium oxychloride (the molar ratio of iron to zirconium is 2 / 1); when preparing adsorbent A6, the metal salt added in step (2) is 0.006 mol ferric chloride and 0.003 mol potassium permanganate (the molar ratio of iron to manganese is 2 / 1).

[0049] In this example, the adsorption effects of different types of metal ion-loaded iron-based chitosan adsorbents on As(III) in water were compared. Figure 3 As shown. Figure 3 It can be seen that the adsorption amount of As(Ⅲ) is A2>A6>A5>A0, which proves that the adsorption effect of bimetallic iron-based chitosan on As(Ⅲ) is better than that of iron-based chitosan, and the adsorption effect of lanthanum-loaded bimetallic iron-based chitosan is better than that of zirconium or manganese-loaded bimetallic iron-based chitosan.

[0050] The above embodiments are only some implementation methods of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention.

[0051] Example 4

[0052] The adsorption capacity of a lanthanum-loaded bimetallic iron-based chitosan adsorbent (A3) and an iron-based chitosan adsorbent (A0) of the present invention for As(III) at different pH values ​​was investigated, comprising the following steps:

[0053] Weigh 0.03 g of a lanthanum-loaded bimetallic chitosan adsorbent (A3) and add it to 30 ml of a 60 mg / LAs(III) solution (pH 3.0-11.0). Adsorb it in a constant temperature water bath oscillator for 24 h (25°C, 150 rpm). After filtering the water sample through a 0.45 μm filter membrane, the arsenic concentration is determined.

[0054] In this example, the preparation method of the lanthanum-loaded bimetallic iron-based chitosan adsorbent (A3) used is the same as that in Example 1.

[0055] In this example, the adsorption effects of A3 and A0 on As(III) in water at different pH values ​​were compared. Figure 5 As shown. Figure 5It can be seen that with the increase of pH, the adsorption amount and removal rate of adsorbent A3 for As(Ⅲ) first increased and then decreased, and the adsorption amount remained at 48.67 mg / g, which was 15.07 mg / g higher than that of A0, and the removal rate was increased by 25.11%. At pH = 7, the maximum value was reached, at which the adsorption amount was 50.80 mg / g and the removal rate was 84.66%. This shows that the adsorption capacity of iron-based chitosan adsorbent for As(Ⅲ) is less affected by pH after La modification.

Claims

1. A method for preparing a bimetallic iron-based chitosan adsorbent and its application in removing As(III) from water, characterized in that: The following steps are involved: (1) dissolving chitosan powder in acetic acid solution and continuously stirring until completely dissolved to obtain a light yellow chitosan solution; (2) pouring the same volume of metal mixed solution (iron-lanthanum, iron-zirconium, iron-manganese metal ion mixed solution) as the chitosan solution into the chitosan solution, and stirring continuously for 0.5 to 1 h to obtain a metal ion / chitosan mixed solution; (3) slowly adding a precipitant to the metal ion / chitosan mixture to precipitate chitosan until the pH of the mixture reaches 7.0±0.1, thereby obtaining a chitosan suspension; (4) stirring the suspension obtained in step (3) continuously for 1.5 h with a stirrer; (5) After stirring, the suspension was placed in a water bath at 60°C for 24 h; (6) The suspension after water bath was centrifuged, and the supernatant was discarded to obtain chitosan precipitate. The precipitate was washed three times and then freeze-dried for 24 hours, ground into powder and passed through a 200-mesh sieve to obtain a bimetallic iron-based chitosan adsorbent.

2. The preparation method of the bimetallic iron-based chitosan adsorbent according to claim 1 and its application in removing As(III) from water, characterized in that: The concentration of the chitosan solution in step (1) is 10-60 g / L, and the concentration of the acetic acid solution is 1%-5%.

3. The preparation method of the bimetallic iron-based chitosan adsorbent according to claim 1 and its application in removing As(III) from water, characterized in that: The metal mixture in step (2) includes three types, namely, iron-lanthanum, iron-zirconium, and iron-manganese metal ion mixtures, and the preparation method thereof is: weigh a certain amount of iron salt and lanthanum salt, zirconium salt or potassium permanganate and dissolve them in the acetic acid solution described in step (1).

4. The preparation method of the bimetallic iron-based chitosan adsorbent and its application in removing As(III) from water according to claim 1, characterized in that: The precipitant in step (3) is sodium hydroxide or potassium hydroxide solution, and its concentration is 0.5-5 mol / L.

5. The preparation method of the bimetallic iron-based chitosan adsorbent and its application in removing As(III) from water according to claim 1, characterized in that: The three times of washing in step (6) are washing with anhydrous ethanol and deionized water three times respectively.

6. The preparation method of the bimetallic iron-based chitosan adsorbent and its application in removing As(III) from water according to claim 1, characterized in that: The continuous stirring speed in steps (1)-(4) is 100 to 300 rpm.

7. The preparation method of the bimetallic iron-based chitosan adsorbent and its application in removing As(III) from water according to claim 3, characterized in that: The iron salt is ferric chloride or ferric nitrate, the lanthanum salt is lanthanum chloride or lanthanum nitrate, and the zirconium salt is zirconium oxychloride; the concentration of the iron salt is 0.12 mol / L; the molar ratio of the iron salt to the lanthanum salt, zirconium salt or potassium permanganate is 1:1 to 4:

1.

8. The bimetallic iron-based chitosan adsorbent obtained by the preparation method according to any one of claims 1 to 7.

9. The bimetallic iron-based chitosan adsorbent according to claim 8 is used to remove As(III) from water.